Intraosseous Fixation Compared to Plantar Plate Fixation for First Metatarsocuneiform Arthrodesis: A Cadaveric Biomechanical Analysis. (November 2014) - Roth, Klaus Edgar; Peters, Jennifer; Schmidtmann, Irene; Maus, Uwe; Stephan, Daniel; Augat, Peter
Background: Metatarsocuneiform (MTC) fusion is a treatment option for management of hallux valgus. We compared the biomechanical characteristics of an internal fixation device with plantar plate fixation. Methods: Seven matched pairs of feet from human cadavers were used to compare the intramedullary (IM) device plus compression screw to plantar plate combined with a compression screw. Specimen constructs were loaded in a cyclic 4-point bending test. We obtained initial/final stiffness, maximum load, and number of cycles to failure. Bone mineral density was measured with peripheral quantitative computed tomography. Performance was compared using time to event analysis with number of cycles as time variable, and a proportional hazard model including shared frailty model fitted with treatment and bone mineral density as covariates. Results: On average the plates failed after 7517 cycles and a maximum load of 167 N, while the IM-implants failed on average after 2946 cycles and a maximum load of 69 N. In all pairs the 1 treated with IM-implant failed earlier than the 1 treated with a plate (hazard ratio for IM-implant versus plate was 79.9 (95% confidence interval [6.1, 1052.2], P = .0009). The initial stiffness was 131 N/mm for the plantar plate and 43.3 N/mm for the IM implant. Initial stiffness ( r = .955) and final stiffness ( r = .952) were strongly related to the number of cycles to failure. Bone mineral density had no effect on the number of cycles to failure. Conclusion: Plantar plate fixation created a stronger and stiffer construct than IM fixation. Clinical Relevance: A stiffer construct can reduce the risk of nonunion and shorten the period of non-weight-bearing.